Melamine negatively affects testosterone synthesis in mice. (December 2016) - Sun, Jiarui; Cao, Yinan; Zhang, Xinchen; Zhao, Qiling; Bao, Endong; Lv, Yingjun
Abstract: Several studies have found that melamine causes damage to the testes, epididymis and sperm. However, few studies have investigated the effect of melamine on the synthesis of testosterone, which plays an import role in testicular development and spermatogenesis. In present study, mice were orally administrated with 2, 10 or 50 mg/kg of melamine for 28 days. In these groups, various abnormalities were observed including disruption of the seminiferous tubule structure, an increased necrotic germ cells and sperm abnormalities, and a reduced sperm count. Melamine exposure also decreased the level of serum testosterone and levels of testicular StAR, P450scc and 17β-HSD. In addition, melamine exposure reduced the number of Leydig cells. Taken together, these results indicate that melamine exposure reduces the level of testosterone through down-regulation of StAR and testosterone synthetic enzyme expression and also a decreased number of Leydig cells. This may further affect testicular development and lead to sperm damage. Highlights: Melamine exposure decreased the level of serum testosterone. Melamine exposure reduced the testosterone synthetic enzyme expression. Melamine exposure decreased the number of Leydig cells.